Umedalen Skulptur 2000. - Andersson, Stefan; Galleri Stefan Andersson, Umea (Umea : Umedalens skulpturpark, 2000)
Cáven, Kari ; Dean, Max ; Gudmundsson, Sigurdur ; Winter, Wolfgang ; Hörbelt, Berthold ; Kentridge, William ; Kruse, Peter ; Lundin, Ulf ; Marclay, Christian ; Miyajima, Tatsuo ; Niemelä, Jaakko ; Renström, Anna ; Rollof, Ulf ; Rönnlund, Anders ; Saunders, Nina ; Spitzer, Serge ; Tällström, Olov ; Yanagi, Yukinori ; Zhu, Lu Ming ; Balka, Miroslaw ; Bergström, Bigert & ; Cragg, Tony (Anthony) ; Englund, Lars ; Gianakos, Cristos ; Gromley, Antony ; Gunnars, Carina ; Hake, Claes ; Berlin, Meta Isaeus - ; Kapoor, Anish ; Kirschenbaum, Bernard ; Kjellgren, Jonas ; Naraha, Takashi ; Nonas, Richard ; Persson, Roland ; Rheinsberg, Raffael ; Schwartz, Buky ; Not Vital ; Wolgers, Dan ; Aberg, Mikael
Umedalen Skulptur 2000, Umedalens skulpturpark, Umea, 2000
Engels & Zweeds
kunstcatalogus
Keywords: Umea